Study on influence of cross section shape evolution on crashworthiness of multicellular square tubes - CAI Zhenzhen; DENG Xiaolin; HUANG Cuiping; XIE Zhaoping; WEI Xiaoyan (Jixie qiangdu)
Taking multicellular square tubes as the research object, the influence of the evolution of cross section shape on the energy absorption of the structure of multicellular square tubes was studied by using the verified finite element model. The results show that, under the same mass conditions, the multicellular tubes with the best energy absorption k=0.25 increased by 26.34% compared with those with the worst energy absorption k=0.40. Under the same wall thickness, the energy absorption with k=0.25 and the specific energy absorption of the multicellular tubes were 311.69% and 73.80% higher respectively than that of the ones with k=0, and the crushing force efficiency was increased by 52.51%. Finally, the parametric study of shape coefficient and wall thickness on the structural crashworthiness was carried out systematically. The research results can provide a reference for innovative design of multicellular square tubes.